PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA (PERSERO) KOTA PADANG - Diawati, Prety; Noorsyafira, Nabilla; Sugesti, Hesti; ismail, Hariadi (Universitas Logistik dan Bisnis Internasional, 2024)
This study aims to determine the effect of reward on employee performance and the effect of punishment on employee performance of PT. Pos Indonesia (Persero) Padang City. With rewards and punishments, it can help the management of human resources that have the potential to improve their performance within the company. This research consists of the theory of human resource management, and the theory of reward, punishment, and employee performance, as well as previous research, frameworks, and hypotheses. This study uses causal associative with a quantitative approach. The population of this study was 133 employees and the sample in this study was 52 employees based on the non-probability sampling technique using the Purposive Sampling Method. Data were collected by using a questionnaire that had been tested for validity and reliability. The data analysis technique used multiple linear regression. Based on the results of the research that the author has researched, it can be concluded that the hypothesis testing for reward and punishment variables on employee performance, based on the F test it was found that H3 was accepted = there was a positive and significant influence between reward and punishment on employee performance. Reward and punishment affect employee performance, this is based on the R2 value of the variation of reward and punishment can be explained by independent variables that can be influenced by other factors not examined in this study. Suggestions from the author to the leadership of PT. Pos Indonesia (Persero) Padang City, to manage the rewards that have been given so far to be adjusted to the standard of work that has been completed by employees, so that employees feel more concerned about their welfare by the company.